RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE AND THE INCIDENCE OF ARI IN TODDLERS AT THE HELVETIA MEDAN COMMUNITY HEALTH CENTER - Sri Wahyuni; Sri Ilawati; Leli Herawati; Siti Nur Rahma Nasution (LPPM Universitas Abdurrab, 2025)
ABSTRACT Acute Respiratory Infections (ARI) are a major cause of morbidity among children under five, with a high prevalence in Indonesia, particularly in the 1–4 year age group. Maternal knowledge plays a critical role in preventing ARI. This study aimed to determine the relationship between maternal knowledge and the incidence of ARI among toddlers at UPT Puskesmas Medan Helvetia in 2024. The study employed a cross-sectional design with accidental sampling, involving 20 respondents. A questionnaire was used as the research instrument. Chi-Square test results showed a significant relationship between maternal knowledge and ARI incidence in toddlers (p-value = 0.025). Greater health education efforts are needed to improve maternal knowledge and reduce ARI cases in children Keywords: ARI, Maternal Knowledge, Toddlers